2004
DOI: 10.1159/000075035
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Degradation Rate for Collagen Chambers Used for Regeneration of Peripheral Nerves over Long Gaps

Abstract: The experimental study of peripheral nerve regeneration has depended heavily on the use of a nerve chamber in which the stumps of the transected nerve are inserted. A large variety of chamber fillings and chamber types have been used in an effort to induce a higher quality of regeneration across the gap initially separating the two stumps. In this study we studied the morphology of nerves regenerated across a 15 mm gap following implantation of a series of five chambers. The chambers were fabricated from type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 51 publications
1
106
0
Order By: Relevance
“…The fibrillar structure of the collagen is maintained throughout manufacture, permitting construction of a tubular matrix that has excellent mechanical strength and defined permeability. 3,30,45 The level of functional recovery achieved with the NeuraGen conduit has been equivalent to direct suture repair of short-segment defects in several experiments in both rats and primates. 4 The use of NeuraGen nerve guides in combination with cultured autologous SCs could expand the clinical potential of the nerve guide, permitting the repair of a larger array of peripheral nerve injuries, even those with a lengthy gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibrillar structure of the collagen is maintained throughout manufacture, permitting construction of a tubular matrix that has excellent mechanical strength and defined permeability. 3,30,45 The level of functional recovery achieved with the NeuraGen conduit has been equivalent to direct suture repair of short-segment defects in several experiments in both rats and primates. 4 The use of NeuraGen nerve guides in combination with cultured autologous SCs could expand the clinical potential of the nerve guide, permitting the repair of a larger array of peripheral nerve injuries, even those with a lengthy gap.…”
Section: Discussionmentioning
confidence: 99%
“…67 To circumvent this potential problem, Lewis rats could be used as an alternative for future walking track studies, since it has been suggested that this strain is less prone to autophagia than are Fischer rats. 12,21,30,39 Our laboratory has performed reversed autografts in male Lewis rats by following the same protocol applied in the current study, with 4-and 16-week survival times. The Lewis rats displayed little to no autotomy behavior.…”
Section: Walking Track Analysis Sfi and Autotomy Scoresmentioning
confidence: 99%
“…Collagen-glycosaminoglycan (CG) scaffolds are regulatory compliant ECM analogs that have been applied to a wide range of regenerative medicine applications, both in vivo for soft tissue applications such as dermis, peripheral nerves, conjunctiva, brain, and cartilage [9][10][11][12] as well as in vitro as three-dimensional (3D) templates to probe various cellular activities, including adhesion, proliferation, migration, and differentiation. [13][14][15][16][17] CG scaffolds have also been adapted for a variety of orthopedic applications covering osteochondral, bone, and tendon tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in peripheral nerve regeneration applications, it has been hypothesized that hydrogel implants must be degradable to avoid physical inhibition of nerve growth and that the optimal degradation half-life of these implants should match the rate of nerve regeneration, approximately 2-4 weeks. [32][33][34][35] In an effort to mimic potential physiological conditions present in such neuronal applications, biologically relevant tPA and uPA concentrations were approximated by performing an enzymelinked immunosorbent assay (ELISA) on PC-12 neuronal-like culture supernatants. These decreased enzyme conditions resulted in the predictable extension of scaffold degradation rate trends over a one-month period and place our hydrogels within the proposed optimal degradation rate range for neuronal materials (Fig.…”
mentioning
confidence: 99%